Leveraging Human Capital for Performance Enhancement in Indonesia Technology Sector - Arsyah, Teguh Dwi; Pakri, Pakri (Privietlab, 2024)
This study analyzes the impact of human capital on the performance of technology companies in Indonesia, focusing on key variables such as education level, work experience, training and development, employee retention, and innovation capacity. This study employed a quantitative approach, utilizing data collected from 150 technology companies in Indonesia through structured questionnaires and company records. Regression analysis was used to evaluate the relationships between the identified human capital variables and company performance, measured by return on assets (ROA). The results reveal that education level, work experience, and innovation capacity significantly and positively affect company performance. Training and development also show a positive, albeit marginally significant, impact, while employee retention has a negative impact on performance. These findings highlight the critical role of human capital in driving technology companies’success in Indonesia. This study suggests that technology companies should prioritize enhancing their employees' educational qualifications, retaining experienced staff, investing in continuous training and development, and fostering a culture of innovation. These strategies can help tech companies sustain their growth and maintain a competitive edge in rapidly evolving markets. This study provides a comprehensive analysis of the specific human capital variables that influence the performance of technology companies in Indonesia. It addresses a gap in the literature and offers valuable insights for business leaders and policymakers on strategic human capital investments to achieve sustainable growth and competitiveness.